SOBREPESO E OBESIDADE ENTRE OS FUNCIONÁRIOS DA UNIVERSIDADE ESTADUAL DE FEIRA DE SANTANA, 2004. - Caires, Noélia Fonseca Ramos (2005)
The obesity is considered, nowadays, serious problem in the public health, it has been constituted as a risk factor for chronic disease in the modern society, as mellitus diabetes, high levels of cholesterol, heart diseases and some kinds of cancer. In order to contribute for the knowledge of prevailing of the overweight and the obesity and its factors of risk, in Feira de Santana city, it has been evaluated a significative sample of the employees of Feira de Santana State University (number of 435 persons 73,2%). We use a questionnaire applied during the interview were identified biological variables (gender, age, birth ability, familiar history of obesity, presence of diseases related to obesity); socioeconomic variables (education and family income) and socio-behavioral (marital status, food habits, practice of physical activity, smoking and consumption of alcoholic drinks).Overweight and obesity were defined through the body mass index (BMI) adapting the established criteria by WHO (1997): values between 25 and 29,9 kg\m2 for overweight and the same values or bigger of 30kg/m2 for obesity. The measure of the abdominal circumference was used to evaluate the risks of heart diseases, adopting the suggested values by Latin American Consensus of obesity (1998): high risk ≥ 94 cm in men and ≥80 in women; very high risk ≥ 102 cm in men and ≥ 88cm in women. In the descriptive analysis were included all the individuals, and in the exploratory analysis were excluded the individuals with low weight (number of 18). Among the 435 participants of the study, the prevailation of overweight and obesity was 31,15% and 10,34% respectively. Among men, these prevailations were of 34,55% and 10,81% ; and among the women of 30,66% and 10,10% respectively. Using the X2 test, it has been observed age, birth condition, family history, daily frequency of food, and kind of physical activity are the variables which show differences in the distribution of weight. For a multivariate analysis it has been made a model using multiple regression with the following variables: age, family history of obesity, birth condition, individuals with and without mates, education, income, practice, duration and frequency of physical activity, number of meals, the use of alcoholic drinks, smoking. It has been done three analyses, the first with men and women; the second only with men and the third only with women. The BMI presented a positive association with family history in all the analyses; the same occurred with income among men and women. In relation to the education the BMI decreases in the answer to the increasing of the level of education only with women. An inverse association occurred with smoking among men and women, and among men isolated. The obtained results point to the necessity of the measures aiming for the control and the prevention of obesity by the official health institutions.